2009
DOI: 10.1089/omi.2008.0050
|View full text |Cite
|
Sign up to set email alerts
|

Combinational Polymorphisms of Seven CXCL12-Related Genes Are Protective against Breast Cancer in Taiwan

Abstract: Many single nucleotide polymorphisms (SNPs) have been found to be associated with breast cancer, but their SNP interactions are seldom addressed. In this study, we focused on the joint effect for SNP combinations of seven CXCL12-related genes involved in major cancer-related pathways. SNP genotyping was determined by PCR-restriction fragment length polymorphism (RFLP) in this study (case = 220, control = 334). Different numbers of combinational SNPs with genotypes called the SNP barcodes from different chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 44 publications
1
43
1
Order By: Relevance
“…In addition, for studies in which controls were matched on the bias of age, six were population-based and only one study was hospital-based. The distribution of genotypes in the controls was consistent with Hardy-Weinberg equilibrium in all studies except for one study [26].…”
Section: Characteristics Of Studiessupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, for studies in which controls were matched on the bias of age, six were population-based and only one study was hospital-based. The distribution of genotypes in the controls was consistent with Hardy-Weinberg equilibrium in all studies except for one study [26].…”
Section: Characteristics Of Studiessupporting
confidence: 69%
“…However, there are only two studies of Asian populations reported [22,26]. Therefore, additional studies are warranted to further validate ethnic differences in the effect of the 936C[T polymorphism on breast cancer risk, especially among Asians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renner et al [15] reported three novel polymorphisms (C702T, C936T, and G1612A) in the 3 0 -untranslated region and found that carriers of the 936T allele had significantly lower VEGF plasma levels than non-carriers, and Krippl et al [16] reported that carriers of the VEGF 936T allele are at decreased risk for breast cancer. However, subsequent reports have shown that the VEGF 936T allele is not associated with breast cancer risk [17][18][19][20][21][22]. The inconclusive nature of these results might be explained by the possible small effect of the polymorphism on breast cancer risk and the relatively small sample size in each of the published studies.…”
Section: Introductionmentioning
confidence: 94%
“…Most studies have addressed the effects of some SNPs, categorizing them as ''not associated,'' and thus concluded that they are not important in cancer or disease risks. It is possible that some SNPs without main effects, or with main effects too small to detect, may interact with others and confer a changed risk for cancers, as demonstrated by Lin et al (64). Especially concerning the influence of CXCL12 genotype rs1801157 on cancer progression, as long as the functional importance of rs1801157 in the expression of the CXCL12 transcript and protein are still unclear.…”
Section: Discussionmentioning
confidence: 99%